Association of genetic risk score and chronic kidney disease in a Japanese population. Issue 6 (29th April 2019) - Fujii, Ryosuke; Hishida, Asahi; Nakatochi, Masahiro; Furusyo, Norihiro; Murata, Masayuki; Tanaka, Keitaro; Shimanoe, Chisato; Suzuki, Sadao; Watanabe, Miki; Kuriyama, Nagato; Koyama, Teruhide; Takezaki, Toshiro; et al.
ABSTRACT: Chronic kidney disease (CKD) is a public health problem worldwide including Japan. Recent genome‐wide association studies have discovered CKD susceptibility variants. We developed a genetic risk score (GRS) based on CKD‐associated variants and assessed a possibility that the GRS can improve the discrimination capability for the prevalence of CKD in a Japanese population. The present study consists of 11 283 participants randomly selected from 12 Japan Multi‐Institutional Collaborative Cohort Study sites. Individual GRS was constructed combining 18 single‐nucleotide polymorphisms identified in a Japanese population. Participants with eGFR <60 mL/min per 1.73 m 2 was defined as case (stage 3 CKD or higher) in this study. Logistic regression analysis was used to examine the association between the GRS and CKD risk with adjustment for sex, age, hypertension and type 2 diabetes mellitus. The frequency of individuals with CKD was 8.3%, which was relatively low compared with those previously reported in a Japanese population. The odds ratio of having CKD was 1.120 (95% confidence interval: 1.042–1.203) per 10 GRS increment in the fully adjusted model ( P  = 0.002). The C‐statistic was significantly increased in the model with the GRS, comparing with the model without the GRS (0.720 vs 0.719, P difference  = 0.008). Increment of the GRS was associated with increased risk of CKD. Additionally, the GRS significantly improved the discriminatory ability of CKD prevalence in a Japanese population; however, the improvement of discriminatory ability brought about by the GRS seemed to be small compared with that of non‐genetic CKD risk factors. Summary at a Glance: This study describes a Genetic Risk Score for chronic kidney disease (CKD) from a Japanese cohort in which CKD‐associated variants were analyzed. The population frequency of CKD was 8.3% amongst 11, 283 participants in the study, with increments in the proposed Genetic Risk Score being associated with increased risk of CKD.